Biodegradability Analysis of Biodegradable foam Combination of Sugarcane Bagasse Fiber and Cassava Starch Based Pineapple Peel During Storage - Irna Dwi Destiana; Raden Naisha Salsabila; Fenny Aprilliani; Roni Suhartono (Agroindustrial Technology Journal, 2024)
Biopolymers like starch and fibers form the basis of biodegradable foam (biofoam), a packaging material that allows nature to modify its properties and facilitate easier decomposition. Due to its easily transformable and decomposable nature, cassava starch can be an alternative for its production. Although cassava starch lacks strength and flexibility, we can utilize natural fibers like sugarcane bagasse and pineapple peel. Assessing the moisture content of biofoam is crucial as it influences the product's durability. Studies on the moisture content of packaging and its biodegradability during storage are necessary due to the close relationship between the moisture content and the degradation process of environmentally friendly packaging. This research aims to understand the moisture content properties of biofoam packaging during storage and its biodegradability. The implementation of this research consists of the production of sugarcane bagasse and pineapple peel fibers, as well as biofoam. This study involves different combinations of sugarcane bagasse and pineapple peel fibers (w/w) such as 5%:25%, 10%:20%, 15%:15%, 20%:10%, and 25%:5%, which are applied three times using the baking process method. The test results show that the variation in the combination of sugarcane bagasse and pineapple peel has a significant effect on the moisture content and disintegration rate of the packaging during storage. The decrease in moisture content increases with the duration of storage. The longer the observation time used, the lower the moisture content value and the higher the percentage of biodegradability in the biofoam